Optical laminate
The adhesive sheet is manufactured by the photocuring method and the anchoring force between it and the optical film is improved, which solves the problems of high energy consumption and CO2 emissions in the prior art, and prevents the peeling of the adhesive sheet and the optical film in the image display device, achieving a more efficient and environmentally friendly image display effect.
Patent Information
- Application Number
- CN202380055640.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-07
AI Technical Summary
The existing adhesive sheet manufacturing process requires a large amount of fuel combustion, resulting in high energy consumption and CO2 emissions. At the same time, in the long-term image display device, the adhesive sheet of the optical laminate and the optical film are easily peeled off, resulting in the failure of the image display function.
The adhesive sheet is manufactured by the photocuring method, and by increasing the anchoring force between the adhesive sheet and the optical film, the adhesive force between the adhesive sheet and the optical film reaches 10.0N/25mm or more, and preventing peeling.
It reduces energy consumption and CO2 emissions in the adhesive sheet manufacturing process, and effectively prevents the peeling of the adhesive sheet from the optical film in the image display device, extending the service life of the image display function.
Smart Images

Figure CN119585653A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to optical stacks. Background Art
[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used to bond the optical films contained in the optical laminate and to bond the optical laminate to the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking.
[0003] An example of a PSA sheet is disclosed in Patent Document 1. In Patent Document 1, the PSA sheet is produced by irradiating a PSA composition with light.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 3052972 Summary of the invention
[0007] Problems to be solved by the invention
[0008] A general adhesive sheet can be manufactured by, for example, the following thermal curing method. First, a crosslinking agent is added to a polymer obtained by polymerizing a polymerizable monomer in an organic solvent to prepare an adhesive composition. The adhesive composition is applied to a substrate such as a release liner, and the organic solvent is removed by heating to form a sheet. Heating and aging are performed as required to complete crosslinking, thereby enabling the manufacture of an adhesive sheet. In this manufacturing process, in order to generate the heat energy required for heating and aging of the solvent, a large amount of fuel such as LNG needs to be burned. In addition, if the organic solvent removed by heating is directly discharged into the atmosphere, there is a hidden danger of causing serious adverse effects on the surrounding environment. Therefore, for organic solvents, in most cases, they are released after being burned in a deodorizing furnace or the like. In this case, not only does the fuel used for burning in the deodorizing furnace become more necessary, but the organic solvent itself is also converted into CO2 due to combustion and discharged into the atmosphere, which is a manufacturing process with a very large CO2 emission.
[0009] In recent years, climate change caused by greenhouse gases has become an urgent issue, and governments around the world have set numerical targets to reduce CO2. In the manufacture of adhesive sheets, it is also required to select a manufacturing process that does not use organic solvents and has low CO2 emissions.
[0010] Compared with the above-mentioned thermal curing method, the method of making an adhesive sheet using light (photocuring method) can reduce the energy required for the formation of the adhesive sheet and the amount of CO2 emissions. However, when an optical laminate is made using an adhesive sheet formed by the photocuring method, an image display device having the optical laminate tends to have problems with image display function after long-term use. This problem occurs particularly significantly when it is repeatedly used in a high temperature environment.
[0011] Therefore, an object of the present invention is to provide an optical layered body capable of suppressing the occurrence of problems in the image display function of an image display device.
[0012] Solutions to the problem
[0013] According to the research of the inventors, when an adhesive sheet formed by a photocuring method is used, there is a tendency that peeling between the adhesive sheet and the optical film is more likely to occur than when an adhesive sheet formed by a thermal curing method is used. It can be inferred that the reason for this tendency is that when an adhesive sheet formed by a thermal curing method is bonded to an optical film, the curing of the adhesive sheet further proceeds on the surface of the optical film, while on the other hand, the curing of the adhesive sheet formed by a photocuring method after bonding to the optical film is hardly performed. This problem occurs particularly significantly when the optical film includes a uniaxially stretched film such as a polarizer and the thickness of the adhesive sheet is less than 30 μm.
[0014] When peeling occurs between the adhesive sheet and the optical film, not only air may intrude therebetween, but the optical film may also sometimes shift from a suitable position. For these reasons, there is a tendency that the image display function of the image display device may have problems. The present inventors have conducted research based on the above insights and have completed the present invention.
[0015] The present invention provides an optical laminate comprising:
[0016] Adhesive sheet formed from a photocurable composition, and
[0017] An optical film comprising at least one selected from a polarizing film and a phase difference film,
[0018] The adhesive sheet and the optical film have an anchoring force of 10.0 N / 25 mm or more.
[0019] Effects of the Invention
[0020] According to the present invention, it is possible to provide an optical layered body capable of preventing problems from occurring in the image display function of an image display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.
[0022] Figure 2A This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0023] Figure 2B This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0024] Figure 3A This is a schematic diagram for explaining an example of the method for producing the optical layered body of the present invention.
[0025] Figure 3B This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0026] Figure 3C This is a schematic diagram for explaining an example of the method for producing the optical layered body of the present invention.
[0027] Figure 4 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention. DETAILED DESCRIPTION
[0028] The optical layered body according to the first aspect of the present invention includes:
[0029] Adhesive sheet formed from a photocurable composition, and
[0030] An optical film comprising at least one selected from a polarizing film and a phase difference film,
[0031] The adhesive sheet and the optical film have an anchoring force of 10.0 N / 25 mm or more.
[0032] In a second aspect of the present invention, for example, in the optical layered body of the first aspect, the anchoring force is larger than 16.0 N / 25 mm.
[0033] In the third aspect of the present invention, for example, in the optical layered body of the first or second aspect, the adhesive force P0 determined by the following test is 8.0 N / 25 mm or less,
[0034] Test: The adhesive sheet was attached to an alkali-free glass, and the adhesive sheet was peeled off from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°, and the force required at this time (adhesive force P0) was measured.
[0035] In a fourth aspect of the present invention, for example, in the optical layered body of the third aspect, the adhesive force P0 is 0.5 to 7.0 N / 25 mm.
[0036] In a fifth aspect of the present invention, for example, in the optical layered body of the third or fourth aspect, the difference between the anchor force and the adhesive force P0 is 5.0 N / 25 mm or more.
[0037] In a sixth aspect of the present invention, for example, in the optical layered body according to any one of the first to fifth aspects, an adhesive force P1 determined by the following test is 10.0 N / 25 mm or more.
[0038] Test: The adhesive sheet was attached to alkali-free glass and heat-treated at 60°C for 100 hours. The adhesive sheet was peeled from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°, and the force required at this time (adhesive force P1) was measured.
[0039] In a seventh aspect of the present invention, for example, in the optical layered body according to any one of the first to sixth aspects, the content of the solvent in the photocurable composition is 5% by weight or less.
[0040] In an eighth aspect of the present invention, for example, in the optical layered body according to any one of the first to seventh aspects, the pressure-sensitive adhesive sheet has a surface that faces the optical film and is subjected to a surface modification treatment.
[0041] In the 9th aspect of the present invention, for example, in the optical laminate of any one of the 1st to 8th aspects, the adhesive sheet has a surface opposite to the optical film, and when the surface is treated with trifluoroethanol, the element ratio R of fluorine on the surface is greater than 0.1 atomic %.
[0042] In a tenth aspect of the present invention, for example, in the optical layered body according to any one of the first to ninth aspects, the optical film has a surface that faces the pressure-sensitive adhesive sheet and has been subjected to a surface modification treatment.
[0043] In the 11th aspect of the present invention, for example, in the optical layered body of any one of the 1st to 10th aspects, the photocurable composition contains a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group.
[0044] In the twelfth aspect of the present invention, for example, in the optical layered body of the eleventh aspect, the monomer group includes a carboxyl group-containing monomer.
[0045] In a thirteenth aspect of the present invention, for example, in the optical layered body of the eleventh or twelfth aspect, the monomer group includes an ether group-containing monomer.
[0046] In a fourteenth aspect of the present invention, for example, in the optical layered body according to any one of the first to thirteenth aspects, the photocurable composition contains a rework improving agent.
[0047] In a fifteenth aspect of the present invention, for example, in the optical layered body according to the fourteenth aspect, the rework improving agent is a silane coupling agent.
[0048] In a sixteenth aspect of the present invention, for example, in the optical layered body according to any one of the first to fifteenth aspects, the photocurable composition contains an isocyanate crosslinking agent.
[0049] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.
[0050] [Embodiments of optical laminate]
[0051] An example of the optical layered body of the present embodiment is shown in Figure 1 . Figure 1 The optical laminate 10 comprises: an adhesive sheet 1 formed of a photocurable composition, and an optical film 2 selected from at least one of a polarizing film and a phase difference film. The adhesive sheet 1 is preferably directly in contact with the optical film 2. The optical laminate 10 may have a structure in which a substrate sheet used when making the adhesive sheet 1 is laminated on the adhesive sheet 1. The optical laminate 10 may be used in the form of an optical film with an adhesive sheet.
[0052] The anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2 is 10.0 N / 25 mm or more. By making the anchoring force F large to this extent, the peeling between the pressure-sensitive adhesive sheet 1 and the optical film 2 can be suppressed, thereby suppressing the occurrence of problems with the image display function of the image display device.
[0053] The anchoring force F of the adhesive sheet 1 and the optical film 2 can be measured by the following method. First, the optical laminate 10 to be evaluated is cut into a width of 25 mm × a length of 150 mm to make a test piece. Next, the entire surface of the optical film 2 possessed by the test piece is superimposed on the stainless steel test plate via a double-sided tape, and a 2 kg roller is reciprocated once to press them together. Next, the adhesive sheet 1 possessed by the test piece is superimposed on the evaluation sheet, and a 2 kg roller is reciprocated once to press them together. The evaluation sheet has a size of 30 mm in width × 150 mm in length, and is not particularly limited as long as it does not peel off from the adhesive sheet 1 during the test. As an evaluation sheet, for example, an ITO film (125Tetoraito OES (manufactured by Oike Industries, Ltd.) etc.) can be used. Next, using a commercially available tensile testing machine, the pressure-sensitive adhesive sheet 1 was peeled off from the optical film 2 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was determined as the anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2. It should be noted that the above test was performed in an atmosphere of 23°C.
[0054] The anchoring force F between the adhesive sheet 1 and the optical film 2 is preferably 11.0 N / 25 mm or more, and can be 12.0 N / 25 mm or more, 13.0 N / 25 mm or more, 14.0 N / 25 mm or more, 15.0 N / 25 mm or more, 16.0 N / 25 mm or more, and can be 17.0 N / 25 mm or more. The anchoring force F is preferably greater than 16.0 N / 25 mm. The upper limit of the anchoring force F is not particularly limited, for example, it is 50 N / 25 mm or less, and can be 30 N / 25 mm or less.
[0055] (Adhesive Sheet)
[0056] The adhesive sheet 1 has surfaces 1a and 1b facing each other. The surface 1a faces the optical film 2. The surface 1b is exposed, for example, on the outside of the optical laminate 10. The surface 1a of the adhesive sheet 1 may or may not be subjected to a surface modification treatment. Depending on the surface 1a subjected to the surface modification treatment, there is a tendency to increase the above-mentioned anchoring force F. Preferably, the surface 1b of the adhesive sheet 1 is not subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, excimer treatment, flame treatment, and the like. The surface 1a is preferably subjected to a corona treatment as a surface modification treatment.
[0057] The surface modification treatment may be implemented in an inert gas atmosphere. By performing the surface modification treatment in a state where the oxygen concentration is reduced by using an inert gas, the risk of ignition of the residual monomer can be reduced. Specifically, the surface modification treatment is preferably performed at an oxygen concentration of 8% by volume or less, more preferably 6% by volume or less, and further preferably 3% by volume or less. If the oxygen concentration is too low, it may cause the introduction of functional groups to the surface of the adhesive sheet by the surface modification treatment to become insufficient, and therefore, the oxygen concentration is preferably 0.01% by volume or more, more preferably 0.1% by volume or more, and particularly preferably 0.5% by volume or more. As specific examples of inert gases, nitrogen and argon can be cited. The surface modification treatment can be implemented at normal pressure (1 atmosphere).
[0058] The conditions of the surface modification treatment as the corona treatment are represented by the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of discharge can be 1kJ / m 2 Above, 2kJ / m 2 Above, 5kJ / m 2 Above, 7kJ / m 2 Above, 10kJ / m 2 Above, 13kJ / m 2 Above, 15kJ / m 2 Above, 20kJ / m 2 Above, 25kJ / m 2Above, 30kJ / m 2 Above, it can be 35kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m 2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below, and further can be 18kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 10 volume % or more and 20.9 volume % or less, the discharge amount can be 1 to 18 kJ / m 2 When the corona treatment is performed in an atmosphere having an oxygen concentration of 0.01 volume % or more and less than 10 volume %, the discharge amount may be 1 to 60 kJ / m 2 By appropriately adjusting the discharge amount of the corona treatment, there is a tendency for the above-mentioned anchoring force F to be improved.
[0059] When the surface 1a of the adhesive sheet 1 is treated with trifluoroethanol, the surface 1a preferably has a large fluorine element ratio R. The element ratio R is, for example, 0.1 atomic % or more, 0.2 atomic % or more, 0.3 atomic % or more, or 0.4 atomic % or more. The upper limit of the element ratio R is, for example, 1.0 atomic % or less.
[0060] The element ratio R can be determined by the following method. First, prepare an adhesive sheet 1 cut into 10 mm in length and 10 mm in width, and adhere the adhesive sheet 1 to the inner wall of the sample tube in such a way that the surface 1a is exposed. Trifluoroethanol (TFE) is added to the sample tube, and the vaporized TFE is brought into contact with the adhesive sheet 1. Thus, the surface 1a can be treated with TFE. According to the treatment with TFE, the carboxyl groups present on the surface 1a react with TFE, and the carboxyl groups are chemically modified. The reaction of the carboxyl groups with TFE is represented by the following formula. It should be noted that the amount of TFE added to the sample tube is adjusted in such a way that all the carboxyl groups present on the surface 1a can react with TFE.
[0061] R-COOH+CF3CH2OH→R-COOCH2CF3
[0062] Next, the adhesive sheet 1 treated with TFE is taken out from the sample tube and placed in an X-ray photoelectron spectroscopy analyzer. The surface 1a of the adhesive sheet 1 is subjected to a wide scan measurement by the X-ray photoelectron spectroscopy analyzer for qualitative analysis. The elements present on the surface 1a are thereby determined. Next, a narrow scan measurement is performed for each element present on the surface 1a. Based on the results of the narrow scan measurement, the element ratio R of fluorine on the surface 1a can be determined. It should be noted that, typically, the fluorine on the surface 1a comes from TFE after reacting with the carboxyl group. Therefore, the element ratio R1 can be used as an indicator of the amount of carboxyl groups present on the surface 1a before treatment with TFE. There is a tendency that the greater the element ratio R is and the more carboxyl groups are present on the surface 1a, the higher the anchoring force F is. It should be noted that according to the research of the present inventors, when the surface 1a is subjected to a surface modification treatment, there is a tendency for the element ratio R to increase.
[0063] As described above, the adhesive sheet 1 is formed by a photocurable composition. The photocurable composition is an adhesive composition that forms the adhesive sheet 1 by irradiating light. The photocurable composition, for example, contains a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group. The content of the (meth)acrylic component in the photocurable composition, that is, the (meth)acrylic monomer and its partial polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet 1 with (meth)acrylic polymer and its cross-linked product as the main component can be formed. However, the photocurable composition is not limited to the above examples. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. (Meth)acrylate refers to acrylate and methacrylate.
[0064] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.
[0065] The amount of the (meth)acrylic acid alkyl ester in 100 parts by weight of the monomer group is, for example, 40 parts by weight or more, and may be 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, and further may be 95 parts by weight or more. It should be noted that when calculating the amount of a specific monomer, the weight of the partial polymer is converted into the weight of each monomer before polymerization.
[0066] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth) acrylic acid, (meth) carboxylethyl acrylate, (meth) carboxylpentyl acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. The amount of the carboxyl-containing monomer in 100 parts by weight of the monomer group is, for example, less than 10 parts by weight, and may be less than 9 parts by weight, less than 8 parts by weight, less than 7 parts by weight, less than 6 parts by weight, less than 5 parts by weight, less than 4.8 parts by weight, less than 4 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, and further may be less than 0.5 parts by weight. The lower limit of the amount of the compounding is, for example, more than 0.1 parts by weight, and may be more than 0.5 parts by weight as the case may be. The monomer group may also not include a carboxyl-containing monomer.
[0067] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic acid monomer, in other words, the (meth) acrylic acid monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl). The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. The amount of the hydroxyl-containing monomer in 100 parts by weight of the monomer group is, for example, less than 20 parts by weight, and may be less than 15 parts by weight, less than 10 parts by weight, less than 7.5 parts by weight, less than 5 parts by weight, less than 4 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, and further may be less than 0.5 parts by weight. The lower limit of the amount of the compounding agent is, for example, 0.01 parts by weight or more, 0.03 parts by weight or more, or 0.05 parts by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.
[0068] The monomer group may include an ether group-containing monomer. The ether group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may include an ether group-containing monomer. The ether group-containing monomer can contribute to the improvement of the anchoring force F described above.
[0069] The ether group-containing monomer is preferably an alkoxy group-containing monomer. Examples of the alkoxy group-containing monomer include alkylene oxide adducts represented by the following chemical formula (1). 1 is a hydrogen atom or a methyl group. 2 is an alkyl group. The alkyl group may be linear or branched. 2 Preferably, it is a straight-chain alkyl group. 2 Examples of the group are methyl and ethyl. n in formula (1) is an integer of 1 to 30, preferably an integer of 1 to 12, and may be an integer of 1 to 5.
[0070] [Chemical formula 1]
[0071]
[0072] Examples of the alkylene oxide adduct represented by formula (1) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, preferably 2-methoxyethyl acrylate (MEA).
[0073] The ether group-containing monomer is not limited to the above-mentioned alkylene oxide adduct. The ether group-containing monomer may have a ring structure, and the ring structure may have an ether group. Examples of the ring structure having an ether group include tetrahydrofuran ring, dihydrofuran ring, Alkane ring, etc. Examples of the ether group-containing monomer having a ring structure are cyclic trimethylolpropane formal (meth)acrylate and tetrahydrofurfuryl (meth)acrylate.
[0074] The amount of the ether group-containing monomer in 100 parts by weight of the monomer group is, for example, 1 part by weight or more, 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, and further 90 parts by weight or more. The upper limit of the amount is, for example, 99 parts by weight or less, and may be 50 parts by weight or less depending on the circumstances. The monomer group may not contain the ether group-containing monomer.
[0075] In the photocurable composition, each of the above monomers may be included in the form of a partial polymer. The partial polymer may be any polymer of a homopolymer and a copolymer. The partial polymer may contribute to the stable formation of the coating layer described later by appropriately increasing the viscosity of the photocurable composition.
[0076] The photocurable composition generally contains a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.
[0077] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The photocurable composition may contain one or more photopolymerization initiators.
[0078] The amount of the photopolymerization initiator in the photocurable composition may be, for example, 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the total of the monomer group and the partially polymerized product thereof.
[0079] The photocurable composition may contain a crosslinking agent. An example of a crosslinking agent is a multifunctional monomer having two or more polymerizable functional groups in one molecule. The multifunctional monomer may be a (meth)acrylic monomer. An example of a multifunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more epoxy groups, aziridine groups, The polyfunctional monomer preferably has two or more C═C bonds in one molecule.
[0080] Examples of the multifunctional monomer include: multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0081] The crosslinking agent may also include other crosslinking agents other than the above-mentioned multifunctional monomer. As other crosslinking agents, isocyanate crosslinking agents may be cited. The photocurable composition may include an isocyanate crosslinking agent as a crosslinking agent, preferably including both the above-mentioned multifunctional monomer and the isocyanate crosslinking agent. The isocyanate crosslinking agent can contribute to the improvement of the above-mentioned anchoring force F.
[0082] As an isocyanate crosslinking agent, a compound having at least two isocyanate groups (isocyanate compound) can be used. The number of isocyanate groups contained in the isocyanate compound is preferably 3 or more. The upper limit of the number of isocyanate groups is not particularly limited, for example, 5. As the isocyanate compound, aromatic isocyanate compounds, alicyclic isocyanate compounds, aliphatic isocyanate compounds, etc. can be cited.
[0083] Examples of the aromatic isocyanate compound include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0084] Examples of the alicyclic isocyanate compound include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0085] Examples of the aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0086] As isocyanate crosslinking agents, there can also be mentioned polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by addition of polyols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by addition of polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.
[0087] The isocyanate crosslinking agent preferably comprises an aliphatic isocyanate compound and / or a derivative of an aliphatic isocyanate compound. The isocyanate crosslinking agent is particularly preferably at least one selected from pentamethylene diisocyanate (PDI) crosslinking agents (PDI and its derivatives) and hexamethylene diisocyanate (HDI) crosslinking agents (HDI and its derivatives). Specific examples of PDI crosslinking agents include isocyanurate modified products of PDI, etc. Specific examples of HDI crosslinking agents include isocyanurate modified products of HDI, biuret modified products, etc.
[0088] The amount of the crosslinking agent in the photocurable composition varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further 0.5 parts by weight or less, relative to 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.
[0089] It should be noted that, when the photocurable composition contains an isocyanate crosslinking agent, the amount of the isocyanate crosslinking agent is, for example, 0.02 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.5 parts by weight or more, and further 1 part by weight or more, relative to a total of 100 parts by weight of the monomer group and its partial polymer. When the photocurable composition contains an isocyanate crosslinking agent, if the amount of the hydroxyl-containing monomer in the photocurable composition is adjusted to a smaller value, there is a tendency for the anchoring force F to be further increased.
[0090] When an isocyanate crosslinking agent is added, the adhesive sheet may sometimes become hard, especially in a high temperature environment. In such a case, the stress relaxation of the adhesive sheet is impaired, and therefore, there is a tendency that the expansion and contraction stress of the optical film is easily transmitted to the interface between the adhesive sheet and the adherend, and it is easy to peel off. In the case where the anchoring force between the adhesive sheet and the optical film can be ensured by a method other than adding an isocyanate crosslinking agent, it is preferred that the photocurable composition does not contain an isocyanate crosslinking agent.
[0091] The photocurable composition may further include a reoperation improving agent. The reoperation improving agent is a component that reduces the adhesion between the adhesive sheet 1 and the adherend (for example, the adhesion P0 described later) by segregating on the surface of the adherend when the adhesive sheet 1 is attached to the adherend such as alkali-free glass or a transparent conductive layer.
[0092] The reoperation improving agent may be, for example, a silane coupling agent having an alkoxysilyl group, preferably having a polar group while having an alkoxysilyl group. In the reoperation improving agent, specific examples of the alkoxy group contained in the alkoxysilyl group are methoxy, ethoxy, etc. As polar groups, for example, carboxyl groups, acid anhydride groups, epoxy groups, etc. may be mentioned. The carboxyl group may be a group generated by hydrolyzing an acid anhydride group. As acid anhydride groups, for example, carboxylic anhydride groups such as succinic anhydride groups, phthalic anhydride groups, and maleic anhydride groups may be mentioned. The reoperation improving agent may also have an ether group other than an epoxy group, and may also have a polyether skeleton.
[0093] The reoperation improving agent preferably has at least one selected from an acid anhydride group and an epoxy group. When a reoperation improving agent having an acid anhydride group or an epoxy group is used, there is a tendency to improve the adhesion (adhesion P1 described later) between the adhesive sheet 1 and the glass by performing a heat treatment after the adhesive sheet 1 is attached to the alkali-free glass.
[0094] Examples of the rework improving agent include alkoxysilane compounds having a polar group, organopolysiloxane compounds having a polar group and an alkoxysilyl group, and polyether compounds having an alkoxysilyl group.
[0095] Examples of the alkoxysilane compound having a polar group include 2-trimethoxysilylethylsuccinic anhydride, 3-trimethoxysilylpropylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-12-967C"), 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.
[0096] Examples of the organopolysiloxane compound having a polar group and an alkoxysilyl group include an acid anhydride group-containing oligomer silane coupling agent (trade name “X-24-9591F”) and an epoxy group-containing oligomer silane coupling agent (trade names “X-41-1053”, “X-41-1059A”, “X-41-1056”, “X-40-2651”, etc.) manufactured by Shin-Etsu Chemical Co., Ltd.
[0097] Examples of the polyether compound having an alkoxysilyl group include MS polymers S203, S303, and S810 manufactured by Kaneka Corporation, SILYL EST250, EST280, SAT10, SAT200, SAT220, SAT350, and SAT400 manufactured by Asahi Glass Co., Ltd., and EXCESTAR S2410, S2420, and S3430 manufactured by Asahi Glass Co., Ltd.
[0098] Relative to the total of 100 parts by weight of the monomer group and its partial polymer, the amount of the reoperation improving agent in the photocurable composition is, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.5 parts by weight or more, and further 0.6 parts by weight or more. The upper limit of the amount is, for example, 10 parts by weight or less, 5 parts by weight or less, and further 1 part by weight or less. The photocurable composition may not contain the reoperation improving agent.
[0099] The photocurable composition may contain additives other than those mentioned above. Examples of additives include silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, antioxidants, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet absorbers, except for chain transfer agents and reworkability improvers.
[0100] The content of the solvent in the photocurable composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The photocurable composition may contain substantially no solvent. Substantially containing no solvent means that a solvent from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0101] The viscosity of the photocurable composition is preferably 5 to 150 poise. The photocurable composition having a viscosity within the above range is particularly suitable for forming a coating layer described below.
[0102] The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 98% or more, or even 99% or more.
[0103] The gel fraction of the pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.
[0104] The creep amount of the adhesive sheet 1 is, for example, 500 μm or less, 300 μm or less, 180 μm or less, 160 μm or less, 150 μm or less, 100 μm or less, or 50 μm or less. The lower limit of the creep amount is, for example, 5 μm or more, 10 μm or more, or 20 μm or more.
[0105] The creep amount of the adhesive sheet 1 can be evaluated as follows (see Figure 2A and Figure 2B ). First, a laminate of the adhesive sheet 1 and the support film 51 to be evaluated is cut into a 10 mm × 50 mm strip to prepare a test piece 52. The support film 51 is arranged for the purpose of suppressing the deformation of the load-applying portion of the adhesive sheet 1 to which a load is applied during the test, thereby measuring the creep amount with higher accuracy. The support film 51 can use a resin film such as a polyethylene terephthalate (PET) film. The support film 51 can be an optical film or a laminate including an optical film. The thickness of the support film 51 can be a thickness that does not deform due to the above-mentioned load, for example, 20 to 200 μm. Next, as Figure 2A and Figure 2B As shown, the test piece 52 is attached to the surface of the stainless steel test plate 53 by using the adhesive sheet 1 with a bonding surface of 10 mm in length and 10 mm in width. Figure 2B yes Figure 2ASection BB. The test piece 52 is pasted to the test plate 53 in a manner that does not allow bubbles to be mixed between the test plate 53 and the adhesive sheet 1. In addition, after pasting, it is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the test plate 53 and the adhesive sheet 1. Next, the test plate 53 and the test piece 52 are vertically held in an atmosphere of 25°C in such a manner that the test plate 53 is on top and are placed for at least 5 minutes. With the test plate 53 fixed, a weight of 500g is fixed at the center of the lower end of the test piece 52, and a load 54 of 500gf is applied vertically downward. The creep amount (displacement amount) of the adhesive sheet 1 relative to the test plate 53 at the moment 3600 seconds after the start of the application of the load 54 is measured as the amount of weight dropped. The amount of weight dropped can be measured using a laser displacement meter.
[0106] The thickness of the adhesive sheet 1 is, for example, 500 μm or less, 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. The lower limit of the thickness of the adhesive sheet 1 is, for example, 2 μm or more, and 5 μm or more.
[0107] (Optical Film)
[0108] The optical film 2 has a surface 2a opposite to the adhesive sheet 1. The surface 2a is in contact with the surface 1a of the adhesive sheet 1, for example. The surface 2a of the optical film 2 may be subjected to a surface modification treatment. According to the surface 2a subjected to the surface modification treatment, there is a tendency to improve the above-mentioned anchoring force F. As the surface modification treatment, the surface modification treatment described above for the surface 1a can be cited.
[0109] The surface 2a is preferably subjected to corona treatment as a surface modification treatment. When the surface 2a is subjected to corona treatment, conditions such as the discharge amount can be appropriately adjusted within the range described above for the surface 1a, for example.
[0110] As described above, the optical film 2 includes at least one selected from a polarizing film and a phase difference film. The optical film 2 may be a laminated film including a polarizing film and / or a phase difference film. The optical film 2 may include a film made of glass. However, the optical film 2 is not limited to the above examples.
[0111] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.
[0112] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.
[0113] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further, it can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further, it can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.
[0114] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0115] It should be noted that the film containing (meth) acrylic resin tends to have a low bonding strength with the adhesive sheet. However, in the present embodiment, by applying a surface modification treatment to the surface 2a of the optical film 2, the above-mentioned anchoring force F can be adjusted to a sufficiently high value even when the surface of the protective film containing (meth) acrylic resin corresponds to the surface 2a of the optical film 2.
[0116] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm from the perspectives of strength, workability such as handling properties, and thin film properties.
[0117] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.
[0118] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be provided on the protective film.
[0119] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.
[0120] The polarizing film may be a circular polarizing film.
[0121] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.
[0122] The phase difference film includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303
[0221] ,
[0222] , and
[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0225] and
[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0227] ).
[0123] The specific structure of the retardation film, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.
[0124] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, particularly preferably 3 to 8 μm.
[0125] The phase difference film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.
[0126] (Method for producing optical layered body)
[0127] The optical laminate 10 can be manufactured, for example, by the following method. Figure 3A , Figure 3B As shown in FIG. 1 , a first laminate 15 is prepared which includes a substrate sheet 21, a coating layer 22 containing a photocurable composition, and a release liner 23 in this order. By irradiating the first laminate 15 with light 14, a pressure-sensitive adhesive sheet 1 ( Figure 3C ).
[0128] Typically, the irradiation of the first stacked body 15 with the light 14 can be carried out from one side of the base sheet 21 ( Figure 3A At this time, the light 14 passes through the substrate sheet 21 and reaches the coating layer 22, thereby curing the coating layer 22. However, it should be noted that the irradiation of the light 14 can be implemented from one side of the release liner 23, or from both sides of the release liner 23 and the substrate sheet 21 ( Figure 3B The pressure-sensitive adhesive sheet 1 formed of the coating layer 22 is sandwiched between the base sheet 21 and the release liner 23 to constitute a part of the second laminate 16 until the release liner 23 is peeled off.
[0129] An example of the base material of the release liner 23 (hereinafter, "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0130] The release liner 23 may have the transmittance of the light 14 or may have the same degree of transmittance of the light 14 as the base sheet 21 .
[0131] The thickness of the release liner 23 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0132] The release liner 23 may include a layer other than the lining substrate. The release liner 23 may include a release layer. The release liner 23 may include, for example, a lining substrate and a release layer formed on one side of the lining substrate. The release liner 23 may be used in a manner such that the release layer is on the coating layer 22 side.
[0133] Typically, the release layer is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 23 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.
[0134] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably addition reaction curing type silicone materials. Addition reaction curing type silicone materials are particularly suitable for forming a release layer that takes into account both adhesion and peelability with respect to the adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.
[0135] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.
[0136] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.
[0137] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.
[0138] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.
[0139] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.
[0140] The release layer can be formed, for example, by heating and drying a coating film containing a release agent composition formed on a lining substrate. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.
[0141] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more.
[0142] The release liner 23 may be in the form of a single sheet or in the form of a long strip.
[0143] An example of the base sheet 21 is a resin film. Examples of the resin contained in the base sheet 21 are the same as examples of the resin that can be contained in the backing base.
[0144] It is preferred that the base sheet 21 has excellent transmittance to the light 14 .
[0145] The thickness of the base sheet 21 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0146] The substrate sheet 21 may have a release layer on the surface of the coating layer 22 side. The examples of the release layer and its preparation method that the substrate sheet 21 may have are the same as the examples of the release layer and its preparation method that the release liner 23 may have. It is also possible to have a release layer on both the release liner 23 and the substrate sheet 21. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may be different, for example, the release layer of the substrate sheet 21 may be thicker.
[0147] The base sheet 21 can generally be selected to have a greater release force with the pressure-sensitive adhesive sheet 1 than the release liner 23 .
[0148] The base sheet 21 may be in a single sheet shape or in a long strip shape.
[0149] The first laminate 15 can be formed, for example, by forming a coating layer 22 on a substrate sheet 21 (or a release liner 23), and disposing a release liner 23 (or a substrate sheet 21) on the formed coating layer 22. Alternatively, the first laminate 15 can be formed by coating the photocurable composition so as to flow into a space between the substrate sheet 21 and the release liner 23, which are maintained at a predetermined interval so that their main surfaces face each other.
[0150] The coating layer 22 can be formed by various coating methods such as roll coating, lick roll coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.
[0151] The thickness of the coating layer 22 can be adjusted according to the target thickness of the adhesive sheet 1, and may be, for example, 5 to 500 μm, 5 to 250 μm, 5 to 150 μm, 5 to 100 μm, 5 to 50 μm, 5 to 30 μm, 5 to 25 μm, or even 5 to 20 μm.
[0152] The light 14 irradiated to the first stack 15 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the photocurable composition. The light 14 obtained by cutting off short-wavelength light with a wavelength of less than 300 nm through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 21 caused by the light 14. The light source of the light 14 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0153] The irradiation of the light 14 may be continuous or intermittent.
[0154] The illuminance of the light 14 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 14 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 14 on the first stack 15 is, for example, 100 to 5000 mJ / cm 2 .
[0155] Next, the release liner 23 is peeled off from the second laminate 16 to expose the surface of the adhesive sheet 1. The optical film 2 is arranged on the exposed surface of the adhesive sheet 1 to produce the optical laminate 10. It should be noted that the exposed surface of the adhesive sheet 1 may be subjected to a surface modification treatment before the optical film 2 is arranged.
[0156] (Characteristics of Optical Laminated Body)
[0157] From the viewpoint of reworkability, the adhesive force P0 of the optical layered body 10 determined by the following Test 1 is preferably 8.0 N / 25 mm or less.
[0158] Test 1: The pressure-sensitive adhesive sheet 1 was attached to an alkali-free glass, and the pressure-sensitive adhesive sheet 1 was peeled off from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°. The force required at this time (adhesive force P0) was measured.
[0159] Test 1 is carried out by the following method. First, the optical laminate 10 is cut into a strip of 150 mm in length and 25 mm in width to prepare a test piece. Next, the test piece is attached to the alkali-free glass via the adhesive sheet 1. Alkali-free glass is glass that does not substantially contain alkali components (alkali metal oxides). Specifically, the weight ratio of the alkali components in the glass is, for example, less than 1000 ppm, and further less than 500 ppm. The alkali-free glass is, for example, in the form of a plate and has a thickness of more than 0.5 mm.
[0160] The test piece is pasted to the alkali-free glass using, for example, a laminator, in a manner that does not allow bubbles to be mixed between the alkali-free glass and the adhesive sheet 1. After pasting the test piece, it is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the alkali-free glass and the adhesive sheet 1, so that the adhesive sheet 1 is closely attached to the alkali-free glass. Next, the test piece is peeled off from the alkali-free glass at a peeling speed of 300mm / min and a peeling angle of 90° (measured length 80mm). At this time, the force required to peel the test piece from the alkali-free glass is measured at intervals of 1 time / 0.5s. The average value of the measured values obtained is determined as the adhesive force P0.
[0161] The adhesive force P0 is preferably 7.0 N / 25 mm or less, and may be 6.0 N / 25 mm or less, 5.0 N / 25 mm or less, 4.5 N / 25 mm or less, 4.0 N / 25 mm or less, and further may be 3.5 N / 25 mm or less. The lower limit of the adhesive force P0 is, for example, 0.5 N / 25 mm or more, 1.0 N / 25 mm or more, and further may be 1.5 N / 25 mm or more. The adhesive force P0 is preferably 0.5 to 7.0 N / 25 mm.
[0162] The difference (F-P0) between the anchoring force F and the adhesive force P0 is preferably 5.0 N / 25 mm or more, and can be 6.0 N / 25 mm or more, 7.0 N / 25 mm or more, 8.0 N / 25 mm or more, 9.0 N / 25 mm or more, 10.0 N / 25 mm or more, 11.0 N / 25 mm or more, 12.0 N / 25 mm or more, and further can be 13.0 N / 25 mm or more. The upper limit of the difference (F-P0) is, for example, 20 N / 25 mm or less.
[0163] In view of durability, it is preferred that the adhesiveness of the optical laminate 10 is improved when the pressure-sensitive adhesive sheet 1 is heat-treated in contact with the alkali-free glass. As an example, the adhesive force P1 of the optical laminate 10 determined by the following Test 2 is preferably 8.0 N / 25 mm or more.
[0164] Test 2: The adhesive sheet 1 was attached to the alkali-free glass and heat-treated at 60° C. for 100 hours. The adhesive sheet 1 was peeled from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°. The force required at this time (adhesive force P1) was measured.
[0165] Test 2 can be carried out in the same manner as Test 1, except that the bond between the alkali-free glass and the adhesive sheet 1 is homogenized in an autoclave and then subjected to a heat treatment at 60°C for 100 hours under atmospheric pressure, and the temperature of the test piece is further lowered to room temperature (e.g., 23°C) before the test piece is peeled off from the alkali-free glass.
[0166] The adhesive force P1 is preferably 9.0 N / 25 mm or more, and may be 9.5 N / 25 mm or more, 10.0 N / 25 mm or more, or further may be 10.5 N / 25 mm or more. The upper limit of the adhesive force P1 is, for example, 20 N / 25 mm or less.
[0167] Another example of the optical layered body of the present embodiment is shown in Figure 4 . Figure 4 The optical laminate 11 has a laminated structure in which the adhesive sheet 1A, the optical film 2A, the adhesive sheet 1B, and the optical film 2B are laminated in this order. The optical laminate 11 may have a structure in which the base sheet used when producing the adhesive sheet 1A is laminated on the adhesive sheet 1A.
[0168] In the optical laminate 11, typically, the optical film 2A is a phase difference film, and the optical film 2B is a polarizing film. The adhesive sheet 1B functions as an interlayer adhesive between the optical films 2A and 2B. The adhesive sheet 1B may be one using a known adhesive.
[0169] The optical layered body of the present embodiment can be distributed and stored in the form of a roll body in which a belt-shaped optical layered body is rolled up, or in the form of a single sheet-shaped optical layered body.
[0170] Typically, the optical laminate of this embodiment can be used in an image display device. The image display device can be formed by, for example, bonding the optical laminate 10 or 11 to an image display panel. The bonding is performed, for example, by an adhesive sheet 1. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be used for household appliances, in-vehicle uses, public information displays (PID) uses, etc.
[0171] Example
[0172] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.
[0173] [Polarizing film]
[0174] First, between rollers with different speed ratios, a polyvinyl alcohol film with a thickness of 80 μm was dyed in an iodine solution at a temperature of 30°C and a concentration of 0.3% for 1 minute, while being stretched to 3 times. Next, it was immersed in an aqueous solution at a temperature of 60°C containing boric acid at a concentration of 4% and potassium iodide at a concentration of 10% for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, it was immersed in an aqueous solution at a temperature of 30°C containing potassium iodide at a concentration of 1.5% for 10 seconds for cleaning, and then dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 28 μm. A transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having an inner alicyclic structure was bonded to one side of the polarizer using a polyvinyl alcohol adhesive. Furthermore, a transparent protective film with a thickness of 47 μm formed with a hard coating (HC) on a cellulose triacetate film (manufactured by Konica Minolta, trade name "KC4UY") was bonded to the other side of the polarizer using a polyvinyl alcohol adhesive. The polarizing film was produced by heating and drying in an oven set at 70° C. for 5 minutes. 2 The surface of the polarizing film on the side of the transparent protective film formed of a modified acrylic polymer was subjected to a corona treatment.
[0175] [Release liner A]
[0176] 30 parts by weight of addition reaction curing silicone (LTC761 containing hexenyl polysiloxane, 30% toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of release control agent (BY24-850 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray), and 1:1 volume ratio of toluene / hexane mixed solvent as diluent were mixed to obtain a silicone release agent composition. The concentration of silicone solid content in the release agent composition was 1.0% by weight. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, 75 μm thick) using a wire bar, and heated at 130°C for 1 minute to prepare a release liner A having a release layer (60 nm thick) on one side.
[0177] [Release liner B]
[0178] A release liner B having a release layer (thickness 120 nm) on one surface was prepared by the same method as the release liner A except that the thickness of the release agent composition applied to the liner was changed.
[0179] [Monomer slurry A1]
[0180] 95.2 parts by weight of n-butyl acrylate (BA) and 4.8 parts by weight of acrylic acid (AA), 0.05 parts by weight of 1-hydroxycyclohexyl-phenyl ketone (Omnirad184, manufactured by IGM Resins BV) and 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad651, manufactured by IGM Resins BV) as photopolymerization initiators were placed in a four-necked flask and irradiated with ultraviolet rays in a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet rays were irradiated until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.
[0181] [Monomer slurry A2]
[0182] Monomer syrup A2 was prepared by the same method as that for monomer syrup A1 except that the monomers used were changed as shown in Table 1.
[0183] [Table 1]
[0184]
[0185] The abbreviations in Table 1 are as follows.
[0186] BA: n-butyl acrylate
[0187] AA: Acrylic acid
[0188] HBA: 4-Hydroxybutyl Acrylate
[0189] [Photocurable compositions C1 to C6]
[0190] Next, the monomer syrup, the crosslinking agent, and the reworkability improving agent were mixed so as to have the compositions shown in the following Table 2, thereby obtaining photocurable compositions C1 to C6.
[0191] [Table 2]
[0192]
[0193] The abbreviations in Table 2 are as follows.
[0194] NDDA: 1,9-nonanediol diacrylate
[0195] D376N: Isocyanurate-modified pentamethylene diisocyanate (Mitsui Chemicals, Inc., STABIOD-376N)
[0196] SAT10: A polyether compound having an alkoxysilyl group (Silyl SAT10, manufactured by Kaneka Corporation)
[0197] 9591F: Acid anhydride group-containing oligomer type silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., X-24-9591F)
[0198] 1056: Epoxy-containing oligomer silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., X-41-1056)
[0199] (Example 1)
[0200] The photocurable composition C1 was applied to the release layer of the release liner A using an applicator to form a coating layer (thickness 20 μm). Next, the release liner B was arranged on the formed coating layer to obtain the first laminate. The release liner B was arranged so that the release layer and the coating layer were in contact. Next, the coating layer was exposed to light at an illumination of 2.5 mW / cm 2 The coating layer was photocured by irradiating the release liner A in the first laminate with ultraviolet light (black light source) for 640 seconds to form a second laminate consisting of the release liner A, the adhesive sheet (thickness 20 μm) and the release liner B.
[0201] Next, the release liner B was peeled off from the second laminate, and the polarizing film was placed on the exposed surface of the pressure-sensitive adhesive sheet to obtain an optical laminate of Example 1. The polarizing film was placed so that the surface on the transparent protective film side formed of a modified acrylic polymer was in contact with the pressure-sensitive adhesive sheet.
[0202] (Example 2)
[0203] The release liner B was peeled off from the second laminate and the discharge amount was 61 W / m 2 ·min An optical laminate of Example 2 was obtained by the same method as in Example 1 except that the exposed surface of the pressure-sensitive adhesive sheet was corona-treated and then a polarizing film was disposed on the exposed surface.
[0204] (Examples 3 to 6)
[0205] Except having changed the photocurable composition used as shown in Table 3, it carried out similarly to Example 2, and obtained the optical laminated body of Examples 3-6.
[0206] (Example 7)
[0207] Except having changed the photocurable composition used as shown in Table 3, the optical laminated body of Example 7 was obtained by the same method as Example 1.
[0208] (Comparative Example 1)
[0209] An optical layered body of Comparative Example 1 was obtained by the same method as in Example 6 except that the exposed surface of the pressure-sensitive adhesive sheet was not subjected to corona treatment.
[0210] (Comparative Example 2)
[0211] An optical layered body of Comparative Example 2 was obtained by the same method as in Example 4 except that the exposed surface of the pressure-sensitive adhesive sheet was not subjected to corona treatment.
[0212] (Comparative Example 3)
[0213] An optical layered body of Comparative Example 3 was obtained by the same method as in Example 5 except that the exposed surface of the pressure-sensitive adhesive sheet was not subjected to corona treatment.
[0214] [Anchoring force]
[0215] For the optical laminates of the embodiments and comparative examples, the anchoring force F of the adhesive sheet and the polarizing film was measured by the above-mentioned method. As a double-sided tape, a product name "No.531" manufactured by Nitto Denko Corporation was used. As a stainless steel test plate, a SUS304 plate (width 40 mm × length 120 mm) was used. As an evaluation sheet, an ITO film (125 Tetoraito OES, manufactured by Oike Industries) was used. As a tensile testing machine, an Autograph SHIMAZU AG-I10KN (manufactured by Shimadzu Corporation) was used.
[0216] [Adhesion]
[0217] The optical laminates of the embodiment and the comparative example were subjected to the above-mentioned tests 1 and 2 to measure the adhesive forces P0 and P1. In tests 1 and 2, alkali-free glass (Corning, trade name "EG-XG") with a thickness of 0.7 mm was used. The operation of peeling the test piece from the alkali-free glass was performed using a tensile testing machine (Shimadzu, Autograph SHIMAZU AG-1 10KN).
[0218] [Durability]
[0219] For the optical laminates of the embodiments and comparative examples, the durability (85°C durability) was evaluated by the following method. First, the optical laminate was cut into a strip of 300 mm in length and 220 mm in width to prepare a test piece. Next, the test piece was attached to the surface of an alkali-free glass (manufactured by Corning, trade name "EG-XG") having a thickness of 0.7 mm via an adhesive sheet. The attachment of the test piece to the alkali-free glass was performed using a laminator. After attaching the test piece, it was placed in an autoclave at 50°C and 0.5MPa for 15 minutes to homogenize the bond between the alkali-free glass and the adhesive sheet, so that the adhesive sheet was closely attached to the alkali-free glass. Next, the test piece was heat treated at 85°C for 500 hours under atmospheric pressure. The appearance of the adhesive sheet between the polarizing film and the alkali-free glass was observed with the naked eye, and the durability of the adhesive sheet was evaluated according to the following criteria.
[0220] (Evaluation Criteria)
[0221] A: There is absolutely no change in appearance such as foaming or peeling.
[0222] B: There is slight peeling or foaming of 0.3 mm or less at the edge, but there is no problem in practical use.
[0223] C: There is peeling or foaming of 1 mm or less at the edge.
[0224] D: There is peeling exceeding 1 mm at the edge.
[0225] Furthermore, durability (95° C. durability) was evaluated by the same method and evaluation criteria as above except that the heat treatment conditions were changed to 95° C. for 500 hours.
[0226] [Table 3]
[0227]
[0228] (*1) There is peeling (anchor peeling) between the polarizing plate and the adhesive sheet.
[0229] (*2) There is peeling between the alkali-free glass and the adhesive sheet.
[0230] According to Table 3, compared with the comparative example, the optical laminate of the embodiment in which the anchoring force F between the adhesive sheet and the optical film (polarizing film) is 10.0N / 25mm or more has a good durability at 85°C. In addition, for the optical laminate of the embodiment, even when the durability at 95°C is evaluated, almost no peeling between the polarizing film and the adhesive sheet is confirmed. As such, in the optical laminate of the embodiment, the peeling between the polarizing film and the adhesive sheet is suppressed, so it can be inferred that according to the optical laminate, the image display function of the image display device can be suppressed from having problems.
[0231] Furthermore, as can be seen from Table 3, Examples 4 and 5 also showed good results in durability at 95° C. These laminates are considered to be particularly suitable for applications requiring durability in a high temperature environment, such as automotive applications.
[0232] Industrial Applicability
[0233] The optical layered body of the present invention can be used in, for example, an image display device.
Claims
1. An optical laminate comprising: Adhesive sheet formed from a photocurable composition, and An optical film including at least one selected from a polarizing film and a retardation film. The anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.
2. The optical layered body according to claim 1, wherein: The anchoring force is greater than 16.0N / 25mm.
3. The optical laminate according to claim 1, wherein the adhesive force P0 determined by the following test is 8.0 N / 25 mm or less, Test: The adhesive sheet was attached to an alkali-free glass, and the adhesive sheet was peeled off from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°, and the force required at this time (adhesive force P0) was measured.
4. The optical laminate according to claim 3, wherein: The bonding force P0 is 0.5-7.0 N / 25 mm.
5. The optical layered body according to claim 3, wherein: The difference between the anchoring force and the adhesive force P0 is 5.0 N / 25 mm or more.
6. The optical laminate according to claim 1, wherein the adhesive force P1 determined by the following test is 10.0 N / 25 mm or more, Test: The adhesive sheet was attached to alkali-free glass and heat-treated at 60° C. for 100 hours. The adhesive sheet was peeled from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90°, and the force required at this time (adhesive force P1) was measured.
7. The optical layered body according to claim 1, wherein: The content of the solvent in the photocurable composition is 5% by weight or less.
8. The optical layered body according to claim 1, wherein: The pressure-sensitive adhesive sheet has a surface that faces the optical film and is subjected to a surface modification treatment.
9. The optical layered body according to claim 1, wherein: The adhesive sheet has a surface opposite to the optical film, When the surface is treated with trifluoroethanol, the element ratio R of fluorine on the surface is 0.1 atomic % or more.
10. The optical layered body according to claim 1, wherein: The optical film has a surface facing the pressure-sensitive adhesive sheet and subjected to a surface modification treatment.
11. The optical laminate according to claim 1, wherein: The photocurable composition includes a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group.
12. The optical layered body according to claim 11, wherein: The monomer group includes a carboxyl group-containing monomer.
13. The optical layered body according to claim 11, wherein: The monomer group includes an ether group-containing monomer.
14. The optical layered body according to claim 1, wherein: The photocurable composition includes a reworkability improving agent.
15. The optical layered body according to claim 14, wherein: The reoperation improving agent is a silane coupling agent.
16. The optical layered body according to claim 1, wherein: The photocurable composition includes an isocyanate crosslinking agent.
Citation Information
Patent Citations
Optical display device having polarizing film
JP2012133303A